2017
DOI: 10.20517/2394-5079.2017.40
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum levels of transforming growth factor b1 with disease severity in patients with hepatocellular carcinoma

Abstract: Aim: Transforming growth factor (TGF) is overexpressed by tumor cells like other proteins and growth factors. TGF-β1 is then activated in the extracellular compartment but is unable to control cell proliferation because of the absence or low level of TGF-β1 receptors on the plasma membrane of malignant hepatocytes. This potential mechanism might interrupt the autocrine regulation loop of TGF-β1 and its blocking effect on cell proliferation. TGF-β1 is a multifunctional cytokine involved in the regulation of gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 17 publications
(23 reference statements)
2
5
0
1
Order By: Relevance
“…In this study, patients with HCC had higher serum values of TGF-β1 and higher fibrosis scores (FIB-4) than patients with cirrhosis. Consistent with our results, Lee et al (2012) [ 41 ], Shehata et al (2013) [ 42 ], and Kohla et al (2017) [ 43 ] have found higher serum levels of TGF-β1 in HCC patients than those in cirrhotic patients and controls. Giannelli et al (2011) have stated that TGF-β induces a signaling pathway that initiates hepatic fibrosis and cirrhotic changes ending with HCC [ 33 ], meaning that the profibrogenic TGF-β1 has a promoting role in cancer growth and development [ 17 ].…”
Section: Discussionsupporting
confidence: 92%
“…In this study, patients with HCC had higher serum values of TGF-β1 and higher fibrosis scores (FIB-4) than patients with cirrhosis. Consistent with our results, Lee et al (2012) [ 41 ], Shehata et al (2013) [ 42 ], and Kohla et al (2017) [ 43 ] have found higher serum levels of TGF-β1 in HCC patients than those in cirrhotic patients and controls. Giannelli et al (2011) have stated that TGF-β induces a signaling pathway that initiates hepatic fibrosis and cirrhotic changes ending with HCC [ 33 ], meaning that the profibrogenic TGF-β1 has a promoting role in cancer growth and development [ 17 ].…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, Ji et al reported that high TGFB1 expression was associated with tumor recurrence and worse prognosis after surgical resection of HCC [26]. Kohla et al also found that serum levels of TGF-β1 in HCC patients were associated with more advanced BCLC stages, larger tumors, and tumor vascular invasion [27]. These findings signified the role of TGF-β1 in tumor growth and progression.…”
Section: Discussionmentioning
confidence: 89%
“…As cancer develops, cancer cells become more resistant to the growth inhibitory properties of TGF-β1, and both the cancer cells and the stromal cells often increase the production of TGF-β1 which stimulates angiogenesis and cell motility. Also, it suppresses immune response with the extracellular matrix and increases the interaction of tumor cell leading to greater invasiveness and metastatic potential of the cancer [27].…”
Section: Discussionmentioning
confidence: 99%
“…In the liver, high levels of TGF-b1 play a role in the occurrence of hepatic fibrogenesis, regulation of cell growth, and tumor development. 33 .In a study by Kohla et al (2017), it was also stated that TGF-b1 levels increased with disease severity and progression in hepatocellular carcinoma, and TGF-b1 level could be complementary to alpha fetoprotein (AFP) in the diagnosis of HCC. 34 .…”
Section: Discussionmentioning
confidence: 99%
“…33 .In a study by Kohla et al (2017), it was also stated that TGF-b1 levels increased with disease severity and progression in hepatocellular carcinoma, and TGF-b1 level could be complementary to alpha fetoprotein (AFP) in the diagnosis of HCC. 34 . In this study, there was no significant relationship between serum IL-10 levels and ALD.…”
Section: Discussionmentioning
confidence: 99%